Civilisation approach in Russia and its historical evolution - Shimov, Vsevolod V. (Journal of the Belarusian State University. Sociology, 2021)
The article examines the features of the evolution of the civilisational approach in Russia. The historical stages of the formation of the civilisational approach in Russian political thought, starting from the pre-revolutionary times and ending with the post-Soviet period, are considered. The works of N. Danilevsky, L. Gumilyov, A. Dugin, V. Tsymbursky are analysed. It is concluded that the civilisational approach in Russia was especially in demand due to the specific nature of Russia’s relations with the Western world and within the discussion about Russia’s belonging to European civilisation. In the perspective of the world-system analysis, the development of the civilisational paradigm in Russia was due to its being on the semi-periphery of the capitalist world-system. It has always complicated relations with the Western countries belonging the world-systemic core. The findings can be used within the study of the processes of formation of national and sociocultural identity in the post-Soviet space, as well as in teaching disciplines of the socio-humanitarian block (political science, history of political doctrines).
Keywords: civilisation; civilisational approach; barbarism; Russia; Europe; Asia